Very fast crystallisation of MFe2O4 spinel ferrites (M = Co, Mn, Ni, Zn) under low temperature hydrothermal conditions: a time-resolved structural investigation. Issue 10 (23rd April 2018) - Dolcet, Paolo; Diodati, Stefano; Zorzi, Federico; Voepel, Pascal; Seitz, Christoph; Smarsly, Bernd M.; Mascotto, Simone; Nestola, Fabrizio; Gross, Silvia
Abstract : A low temperature hydrothermal route to produce catalytic transition metal ferrite nanoparticles in a clean and very fast way. Abstract : MFe2 O4 spinel ferrites (M = Co, Mn, Ni, Zn) were synthesised through a low-temperature aqueous route combining co-precipitation of oxalates and hydrothermal treatment at 135 °C. With the objective of gaining a deeper understanding of the structural evolution of the compounds to crystalline materials during the synthetic process, samples were prepared within different reaction times, showing in most cases a fully crystalline habit already after short treatment times. The resulting solids were characterised through several state-of-the-art analytical techniques, both on the atomic (XAS) and mesoscopic (XRPD, SAXS) scales. In parallel, temperature-programmed characterisation was carried out to investigate the evolution of the compounds during the heating process.